The use of tuned filters as an attenuator device of harmonics generated by multipulse converters - Oliveira, P. S. [UNESP]; De Seixas, F. J M [UNESP]; De Freitas, S. C L [UNESP]; De Oliveira, L. C O [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The purpose of this paper is to present a computer model that enables the operation analysis of a tuned filter as an attenuator device of harmonic generated 12 and 18-pulses converters with Y-generalized differential connection. Are presented in this study physical considerations, mathematical modeling and digital simulations in the frequency domain using the software Orcad-Pspice®, which allows a spectral analysis of the harmonic components and supports the search for an optimal filtering process. It is unequivocally demonstrated the feasibility of the application as an alternative to optimize the use of multipulse converters, and enable the operation of this device within the established regulatory standards. The validation of the proposed model is based on results obtained in the time domain using Matlab/Simulink®. © 2011 IEEE.
Keywords: Harmonic attenuator; multipulse converters; tuned filters; Computer models; Differential connection; Digital simulation; Frequency domains; Harmonic components; Mathematical modeling; MATLAB /simulink; Multi-pulse converters; Operation analysis; Optimal filtering; Regulatory standards; Spectral analysis; Time domain; Tuned filter; Models; Optimization; Spectrum analysis; SPICE; Time domain analysis; Harmonic analysis